Thromboelastographyguided transfusion therapy in a pregnant patient with hemorrhagic dengue fever hospitalized in icu. Case report - José Antonio Rojas; Daniel Molano-Franco; Tito Jiménez; Albert Valencia; Rafael Leal; Pablo Méndez; Víctor Nieto; Diego Hernández (Case Reports)
Dengue fever is the biggest public health issue in tropical countries. A significant percentage of patients who suffer from this disease require admission to the intensive care unit (ICU) due to the severity of the clinical picture. This case reports the clinical evolution of an eight-week pregnant woman with dengue fever associated with thrombocytopenia and leukopenia. The patient comes from an endemic area for tropical diseases, fact that led to diagnose dengue fever with hemorrhagic characteristics. During her stay in the ICU, the patient presented with first trimester bleeding and placental hematoma. Therefore, and considering the pregnancy and the risk of loss, the hematological function was monitored through thromboelastography. The transfusion of blood products was decided according to the specific findings. Controlling and reversing the obstetric bleeding process was possible, the patient condition evolved favorably, and she was subsequently discharged from the ICU. This article reports on the usefulness of dynamic monitoring the hematological function using thromboelastography in patients with hemorrhagic dengue fever and special conditions such as pregnancy.